Optimal Horizons for Inflation Targeting - Nicoletta Batini; Edward Nelson (Sveriges Riksbank, 2000)
In this paper we investigate the problem of selecting an optimal horizon for inflation targeting in the United Kingdom. Since there are two key ways of thinking about an optimal horizon, we look at optimal horizons for both of these interpretations. In addition, to see whether our results are robust in the face of model uncertainty, we compute optimal horizons for two different models with divergent structural and dynamic characteristics.
Keywords: E37; E52; E58; 330; Inflation targeting; Horizon; Optimal policy rules; Simple feedback rules; Target